Origin of Performance Differences of Nickel‐Rich LiNi0.9Mn0.1O2 Cathode Materials Synthesized in Oxygen and Air. Issue 3 (6th March 2019) - Zhang, Jiangtao; Tan, Xinghua; Guo, Limin; Jiang, Yi; Liu, Shengnan; Wang, Hanfu; Kang, Xiaohong; Chu, Weiguo
Abstract : Surface state and/or bulk structure, which are determined by different synthesis conditions, have a significant effect on the performance of an electrode material. Distinguishing their individual roles in the performance can provide guidance for the synthesis of high‐performance electrode materials. Cobalt‐free and nickel‐rich LiNi0.9 Mn0.1 O2, a promising cathode material, is synthesized in air and oxygen to show remarkable differences in both surface state and structure using a facile sol–gel method. Li2 CO3 formed at the surface during the synthesis in air results in much poorer performance than in oxygen, which can be significantly improved by the effective removal of Li2 CO3 through ultrasonic treatments without changing the bulk structure, morphology, and size. The surface state, instead of bulk structure, morphology, and size‐related elements like more severe cationic mixing and larger secondary particles, is predominantly responsible for the performance difference between the samples synthesized in air and oxygen, which is beyond the conventional viewpoints on layered compounds. This study provides a new perspective for exploring novel synthesis approaches of high‐performance cobalt‐free and nickel‐rich layered compounds. Abstract : Nickel‐rich LiNi0.9 Mn0.1 O2 layered compounds synthesized in air and oxygen, A‐LNMO and O‐LNMO, show Li2 CO3 layers with different thicknesses, which are predominantly responsible for their different performances. The Li2 CO3 layer of A‐LNMO with larger thickness can be significantly reduced or removed by ultrasonication to remarkably improve its rate capability.